Examining physiological, water relations, and hydraulic vulnerability traits to determine anisohydric and isohydric behavior in almond (Prunus dulcis) cultivars: Implications for selecting agronomic cultivars under changing climate - Álvarez-Maldini, Carolina; Acevedo, Manuel; Estay, Daniela; Aros, Fabián; Dumroese, R. Kasten; Sandoval, Simón; Pinto, Manuel (Frontiers in Plant Science, 2022)
The search for drought tolerant species or cultivars is important to address water scarcity caused by climate change in Mediterranean regions. The anisohydric–isohydric behavior concept has been widely used to describe stomatal regulation during drought, simply in terms of variation of minimal water potential (Ψmin) in relation to pre-dawn water potential (Ψpd). However, its simplicity has sometimes failed to deliver consistent results in describing a complex behavior that results from the coordination of several plant functional traits. While Prunus dulcis (almond) is known as a drought tolerant species, little information is available regarding consistent metrics to discriminate among cultivars or the mechanisms underlying drought tolerance in almond. Here we show a sequence of plant stomatal, hydraulic, and wilting responses to drought in almonds, and the main differences between anisohydric and isohydric cultivars. In a pot desiccation experiment we observed that stomatal closure in P. dulcis is not driven by loss in turgor or onset of xylem cavitation, instead, occurs early in response to decreasing Ψmin that could be related to the protection of the integrity of the hydraulic system, independently of cultivar. Also, we report that anisohydric cultivars of P. dulcis are characterized by maximum stomatal conductance, lower water potentials for stomatal closure and turgor loss, and lower vulnerability to xylem cavitation, which are traits that correlated with metrics to discriminate anisohydric and isohydric behavior. Our results demonstrate that P. dulcis presents a strategy to avoid cavitation by closing stomata during the early stages of drought. Future research should also focus on below-ground hydraulic traits, which could trigger stomatal closure in almond.